Development of Management Information System to Improve Sustainable Competitive Advantage of Nurul Barqi Sejahtera Cooperative - Farliana, Nina; Rusdarti, Rusdarti; Sakitri, Wijang (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to provide cooperative management training to improve the understanding and skills of administrators and supervisors in providing services to members. The location of this community service is at the Nurul Barqi Sejahtera Service Cooperative, Semarang, Central Java Province, with a target of 14 participants consisting of administrators and supervisors. The solution approach is carried out through the workshop method, which includes steps such as initial problem identification, follow-up FGD on institutional management development, development of an integrated cooperative management information system, implementation of an integrated SIM operation workshop, and program evaluation using interview instruments, with source triangulation analysis techniques, and follow-up. The results of this service are that the development of teacher professionalism in managing school cooperatives has been successfully carried out, starting from the problem identification stage and workshops to program evaluations. The results of this service can also increase cooperatives’ competitiveness in a sustainable manner. Challenges faced, such as limited understanding of teachers regarding cooperative development, have been successfully overcome through intensive training and ongoing mentoring.